Factors Affect Tourism Stock Price in Indonesia - Goh, Thomas Sumarsan; Henry, Henry; Toni, Nagian; Erika, Erika; Liem, Gai Sin (International Journal of Communication and Society, 2022)
The study aims to examine which factors affect the tourism stock price more. The study uses weekly exchange rate and tourism stock prices; the inflation, interest rate, and the number of tourism use monthly data. Using descriptive statistics, correlation matrix, augmented Dickey Fuller's unit root test, VAR, the Granger causality test, and Impulse Response. The results show that all the variables in our observations have no causal relationship. Interest rates do not have a causal relationship with exchange rates, inflation, number of tourists, and tourism stock prices. The VAR models show interest rate has a negative impact on tourism stock price, exchange rate, and the number of tourists positively impacting tourism stock price. Inflation has no impact on tourism stock price. A decrease in interest rates will encourage investment to develop a business. A decrease in the IDR exchange rate against the USD will lower the product's price, so foreign tourists will feel that Indonesian goods are getting cheaper; thus, they will spend more and increase the tourism company's share price. Regulators can use the research results by lowering and maintaining the stability of interest rates, exchange rates, inflation, and increasing the number of tourists to Indonesia.Â